Trapped radical behavior of electron beam irradiated polytetrafluoroethylene fine powder at various temperatures - Akihiro Oshima (Nature Portfolio, 2021)
Abstract Polytetrafluoroethylene (PTFE) fine powder with 93% crystallinity was irradiated by an electron beam (EB) at various temperatures under a nitrogen atmosphere. Trapped free radicals in PTFE were studied using electron spin resonance (ESR) spectroscopy. The observed spectra of the samples exposed to air after irradiation at various temperatures showed asymmetrical signals, which are middle-chain type peroxide macroradicals derived from fluoroalkyl radicals. The radical yields at each irradiation temperature increased with increasing absorbed dose, and eventually saturated. The higher irradiation temperature resulted in higher radical yields when compared at the same exposed dose. Furthermore, the G-value of the radicals (G(R·)) increases with increasing irradiation temperatures corresponding to each relaxation and transition temperature. It is concluded that the chain reaction by the fluorine extraction from the main chain due to the end-chain radical generated via β-scission after dissociative electron attachment (DEA) is enhanced by the synergistic effect of heat and radiation.